Emerging importance of dietary phytochemicals in fight against cancer: Role in targeting cancer stem cells. Issue 16 (2nd November 2017) - Singh, Amit Kumar; Sharma, Neelesh; Ghosh, Mrinmoy; Park, Yang Ho; Jeong, Dong Kee
ABSTRACT: Recent years have seen an unpretending increase in research using dietary phytochemicals for targeting cancer and cancer stem cells (CSCs) due to the limited efficacy of conventional chemotherapy and radiotherapy and numerous associated side effects. A large number of dietary phytochemicals using traditional recommendation and experimental approaches have been demonstrated to have anti-proliferative, anti-metastatic, reactive oxygen species (ROS) inducing, anti-angiogenic, pro-apoptotic effects and efficacy in targeting cellular molecules and pathways implicated in malignancy. Researchers have shown the knack of phytochemicals in interfering with the CSCs self-renewal process. Thus, dietary phytochemicals can play a significant role in the cancer therapy owing to the plethora of targets without toxicity. In this review, we have discussed about the basic knowledge of CSCs, their identification, characterization, mechanism of self-renewal pathways (Wnt/β-catenin, Hedgehog, and Notch), features that help in the survival of CSCs and use of phytochemicals to replace chemotherapy. Applications of phytochemicals including curcumin, epigallocatechin-3-gallate (EGCG), resveratrol, lycopene, and sulforaphane for their effect on targeting cancer and in particular CSCs along with their molecular mechanisms responsible for pharmacological action are also discussed.